2009
DOI: 10.1177/0963662509335457
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic stem cell: A climax in the reign of the Brazilian media

Abstract: In the last few years, embryonic stem cell research has been widely debated in Brazil and a “star” in the national media. Because of the notoriety of the issue, the media have sometimes been criticized for oversimplification, exaggeration and distortion. In this context, we analyzed the media during an important time: in 2008, the Federal Supreme Court held historical hearings to decide whether Brazilian scientists could continue using embryonic stem cells. First, we focused on letters sent by readers to one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 10 publications
0
14
0
5
Order By: Relevance
“…Hungary, telephone: + 36 1-482-7350, fax: +36 1-482-7348, e-mail: lilla.vicsek@uni-corvinus.hu. stem cell research that have taken place in different societies such as the United States, the United Kingdom, Germany, Brazil, etc. Ethical controversies featured strongly in the stem cell related media coverage of these countries (Hughes et al 2008, Jurberg et al 2009, Kitzinger 2008a, Kitzinger and Williams 2005, Nisbet et al 2003, Reis 2008, Weingart et al 2008. In this paper we present our research results from a post-socialist society, Hungary, where in contrast, the issue of ethical concerns about the embryo -as we will demonstratehas been basically absent from the political sphere and where it has been only a marginal topic in the media.…”
Section: Introductionmentioning
confidence: 87%
“…Hungary, telephone: + 36 1-482-7350, fax: +36 1-482-7348, e-mail: lilla.vicsek@uni-corvinus.hu. stem cell research that have taken place in different societies such as the United States, the United Kingdom, Germany, Brazil, etc. Ethical controversies featured strongly in the stem cell related media coverage of these countries (Hughes et al 2008, Jurberg et al 2009, Kitzinger 2008a, Kitzinger and Williams 2005, Nisbet et al 2003, Reis 2008, Weingart et al 2008. In this paper we present our research results from a post-socialist society, Hungary, where in contrast, the issue of ethical concerns about the embryo -as we will demonstratehas been basically absent from the political sphere and where it has been only a marginal topic in the media.…”
Section: Introductionmentioning
confidence: 87%
“…For example, in the journal Brazilian Journalism Research, out of the 50 articles on journalism published between 2005 and 2008, only five focused on the news conveyed by the TV 7 . When searching for papers on science and technology content in the newscasts, the number of Brazilian research publications is even smaller, with most papers dealing with science coverage in general in the foreign printed press 8,9,10,11,12 or with specific scientific issues such as nanotechnology, 13,14 biotechnology, 16,17,18 and climate change, 19,20,21,22,23 mostly in foreign media. The identification of the position occupied by science in the media, particularly television, would make it possible to check to what extent Brazilians' demand for this kind of information is met.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to findings of media analyses that reported data from the US, Brazil and the UK (Jurberg et al, 2009;Kitzinger & Williams, 2005;Nisbet et al, 2003;Priest, 2006;Reis, 2008), the Hungarian press analyzed featured stem cell research and treatment more in a positive than in a negative light: the presentation of the benefits outweighed that of costs. Moreover, similarly to the media analysis of , which analyzed human genetics in the UK media, we found that by far the most dominant benefit in the media was medical benefit.…”
Section: Discussionmentioning
confidence: 97%
“…A major concern of the opponents of such research was ethical and moral issues regarding the utilization of embryos. In spite of a controversial image being significantly present, those studies which discussed how negatively or positively stem cell research was depicted, also reported that stem cell research tended to be presented in the media outlets analyzed in the US, UK and Brazil more in a positive light, with an emphasis on potential benefits (Jurberg et al, 2009;Kitzinger & Williams, 2005;Nisbet et al, 2003;Priest, 2006;Reis, 2008). These results fit in with arguments that medical applications of biotechnology are often more positively evaluated in the media than agricultural applications (Bauer, 2005;Marks, Kalaitzandonakes, Wilkins, & Zakharova, 2007).…”
Section: Previous Research On Social Scientific Aspects Of Stem Cell mentioning
confidence: 99%
See 1 more Smart Citation